Assessment of Self-Care Activities Using Diabetes Self-Management Questionnaire in Diabetes Patients - Balgis Balgis; Selfi Handayani; Sumardiyono Sumardiyono; Nur Kholifah Putri Taufan (Jurnal Kesehatan Masyarakat, 2023)
One of the non-communicable diseases found in all regions of the world, including rural areas, is Diabetes Mellitus, caused by a chronic metabolic disorder characterized by increased glucose levels in the blood due to impaired insulin secretion. Diabetic neuropathy is damage to peripheral nerves or peripheral nerves commonly experienced by people with type 2 diabetes mellitus, characterized by excessive pain and decreased sensitivity to touch. The purpose of this study was to determine the self-management carried out by diabetic patients in the city of Surakarta. This study is cross-sectional with a sample of 99 respondents using a purposive sampling technique with inclusion criteria of 40-60 years of age and type 2 DM patients. The tests carried out were the inter-class intercorrelation coefficient test and the Kruskal–Wallis test using SPSS. The results of this study mean the highest interclass correlation coefficient was the diabetic foot care subclass with a value of 0.773 representing the homogeneity of the DMSQ questions and a confidence interval of 0.687-0.839 at 95% with a significance of p 0.05 in each subclass.